Legal and policy barriers to phasing out fossil fuels in the Global South: the case of Mozambique - Di Salvatore, Lea (2025)
This thesis explores the legal and policy barriers to phasing out fossil fuels in the Global South, focusing on Mozambique as a case study. The urgent need for a global fossil fuel phaseout is driven by fossil fuels’ pivotal role in climate change. This thesis highlights the complex interplay between Mozambique’s economic dependency on fossil fuels and the global imperative to reduce greenhouse gas emissions. The analysis is divided into three core chapters, each addressing specific legal and policy challenges. The first chapter critiques the limitations of the UN Climate Regime in fostering a coordinated global approach to phasing out fossil fuel production, particularly for Global South countries like Mozambique. The second chapter investigates the role of international investment law in protecting fossil fuel investments, which poses substantial economic and legal risks to Mozambique and locks it into a high carbon cycle for the foreseeable future. The final chapter scrutinises the influence of official development assistance on Mozambique’s development pathway, revealing that current aid may not be Paris-aligned. The thesis concludes by advocating for a reevaluation of Mozambique’s national policies and international cooperation frameworks to better align with sustainable development goals and climate commitments. It calls for strengthened international cooperation to support Mozambique’s transition away from fossil fuels, emphasising the responsibility of Global North countries to facilitate this shift.